Taming Japan's deflation : the debate over unconventional monetary policy - Park, Gene, 1971-; Katada, Saori N.; Chiozza, Giacomo; Kojo, Yoshiko, 1956- (Cornell studies in money, 2018)
"Discusses how entrenched monetary policy ideas within the Bank of Japan, protected by policy network, inhibited addressing persistent deflation since its de jure independence of 1998"--